Gambaran Regulasi Emosi pada Ibu Bekerja yang Mengalami Konflik Peran Ganda - Pradani, Zalza Putri; Widyastuti (Indonesian Journal Publisher, 2023)
This study aims to determine the description of emotional regulation in working mothers who experience dual role conflict where there is a conflict between work outside the home and household work conflicts. The purpose of this study is to provide an overview of emotional regulation by working mothers who experience dual role conflict and to determine the factors that influence emotional regulation of working mothers who experience dual role conflict. The researcher uses a qualitative approach by focusing on a phenomenon, where mothers experience a dual role conflict between working and being a housewife. The respondents of this study were 3 mothers who worked as employees and had also become housewives who had children and significant others or informants from each respondent amounted to one person. Data collection was done by structured interviews. The results showed that the three respondents could bring up aspects of emotional regulation including aspects of situation selection, situation modification, attention deployment, cognitive change and response modulation. While the factors in the regulation of emotions include gender, cognitive and social support.